"Svoji k svojim!" - Jezernik, Božidar (Etnolog. Nova vrsta (Ljubljana), 2008)
The article analyses how the Slovenian national idea started to develop after the March Revolution of 1848, creating, on the one hand, a feeling of solidarity among all the members of the Slovenian people, regardless of the provincial borders, and erecting, on the other hand, a wall separating them from their fellow citizens, who belonged to other peoples.
Keywords: ethnology; etnologija; history; zgodovina; narodno prebujenje; narodna zavest; slovenstvo; marčna revolucija; Slovenia; Slovenija